Downregulated miR-181a alleviates H2O2-induced oxidative stress and cellular senescence by targeting PDIA6 in human foreskin fibroblasts - Yan Huang; Huimin Yan; Yanqing Yang; Jinfei Zhou; Qijun Xu; Hu Meng (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Oxidative stress is strongly associated with cellular senescence. Numerous studies have indicated that microRNAs (miRNAs) play a critical part in cellular senescence. MiR-181a was reported to induce cellular senescence, however, the potential mechanism of miR-181a in hydrogen peroxide (H2O2)-induced cellular senescence remains obscure. Objective The aim of this study is to investigate the role and regulatory mechanism of miR-181a in H2O2-induced cellular senescence. Methods Human foreskin fibroblasts (HFF) transfected with miR-181a inhibitor/miR-NC with or without H2O2 treatment were divided into four groups: control + miR-NC/miR-181a inhibitor, H2O2 + miR-NC/miR-181a inhibitor. CCK-8 assay was utilized to evaluate the viability of HFF. RT-qPCR was used to measure the expression of miR-181a and its target genes. Protein levels of protein disulfide isomerase family A member 6 (PDIA6) and senescence markers were assessed by western blotting. Senescence-associated β-galactosidase (SA-β-gal) staining was applied for detecting SA-β-gal activity. The activities of SOD, GPx, and CAT were detected by corresponding assay kits. The binding relation between PDIA6 and miR-181a was identified by luciferase reporter assay. Results MiR-181a inhibition suppressed H2O2-induced oxidative stress and cellular senescence in HFF. PDIA6 was targeted by miR-181a and lowly expressed in H2O2-treated HFF. Knocking down PDIA6 reversed miR-181a inhibition-mediated suppressive impact on H2O2-induced oxidative stress and cellular senescence in HFF. Study limitations Signaling pathways that might be mediated by miR-181a/PDIA6 axis were not investigated. Conclusion Downregulated miR-181a attenuates H2O2-induced oxidative stress and cellular senescence in HFF by targeting PDIA6.